THE INFLUENCE OF GROUP WORK TOWARDS STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT THE FIRST SEMESTER OF THE TENTH CLASS AT SMA YADIKA NATAR LAMPUNG SELATAN IN 2015/2016 - Alfiawati, Riska (Lentera: Jurnal Ilmiah Kependidikan, 2018)
There are many technique which can be used in teaching and learning process an one of them is group work. Group work has the power to encourage the writing habit in a good a way. It enables students to work together on writing in different ways. In writing, the technique group work can helps the students to improve their knowledge and add their vocabulary from their mistakes in writing. The objectives of this research was to know the influence of group work towards students’ descriptive writing ability at the first semester of the tenth class at SMA YADIKA NATAR Lampung Selatan. To conduct this research, the writer used experimental method and the number of population was 75 students. The writer took two classes as the sample of this research. The writer used total sampling technique to take the sample of this research. To know the students’ ability, the writer gave writing test that was by asking the students to write a paragraph about descriptive text at least 150 words. To know the influence of group work towards students’ descriptive writing abilty. After analyzing the data by using , it was found that at significance level 1% and 5% = 2.66 and 1.99 and t ratio 3.97 it menas that , so there is positive influence of using group work towards students’ descriptive writing abilty at the second semseter of the tenth class at SMA YADIKA NATAR Lampung Selatan in 2014/2015. Therefore, the English teacher can use group work is suitable technique for teaching writing, especially in descriptive writing ability in the class.